Penerapan Senam Reumatik Sebagai Upaya Penurunan Tingkat Nyeri Sendi Pada Penderita Rheumatoid Arthritis - Munawaroh, Madinatul; Nopiansyah, Fepta; Kasumah, Yanti; Putri, Yesi; Putra, Soska Dwi; Rohani, Tuti; Azissah, Danur (Jurnal Dehasen Mengabdi, 2025)
Rheumatoid arthritis is a significant health issue affecting the elderly population in RT 05, Ponorogo Village, Lubuklinggau Utara II District. A lack of knowledge about this disease and limited skills in its prevention and management pose major challenges. The condition causes joint pain that disrupts daily activities, necessitating effective solutions. The aim of this community service initiative is to provide education about rheumatoid arthritis and implement therapeutic exercises, specifically rheumatic gymnastics, as a non-pharmacological intervention.The methods employed include educational outreach on rheumatoid arthritis and regular sessions of rheumatic gymnastics. These exercises are designed to enhance joint flexibility, improve blood circulation, and alleviate pain experienced by sufferers.Results from the activities indicate a notable increase in participants' understanding of rheumatoid arthritis management and a decrease in pain levels following the implementation of rheumatic gymnastics. Consequently, this initiative successfully offers a meaningful solution to improve the quality of life for the elderly and mitigate the adverse effects of the disease.